Impaired Cerebellar Functional Connectivity in Schizophrenia Patients and Their Healthy Siblings - Collin, Guusje; Hulshoff Pol, Hilleke E.; Haijma, Sander V.; Cahn, Wiepke; Kahn, Rene S.; van den Heuvel, Martijn P. (Frontiers in Psychiatry, 2011)
The long-standing notion of schizophrenia as a disorder of connectivity is supported by emerging evidence from recent neuroimaging studies, suggesting impairments of both structural and functional connectivity in schizophrenia. However, investigations are generally restricted to supratentorial brain regions, thereby excluding the cerebellum. As increasing evidence suggests that the cerebellum contributes to cognitive and affective processing, aberrant connectivity in schizophrenia may include cerebellar dysconnectivity. Moreover, as schizophrenia is highly heritable, unaffected family members of schizophrenia patients may exhibit similar connectivity profiles. The present study applies resting-state fMRI to determine cerebellar functional connectivity profiles, and the familial component of cerebellar connectivity profiles, in 62 schizophrenia patients and 67 siblings of schizophrenia patients. Compared to healthy control subjects, schizophrenia patients showed impaired functional connectivity between the cerebellum and several left-sided cerebral regions, including the hippocampus, thalamus, middle cingulate gyrus, triangular part of the inferior frontal gyrus, supplementary motor area and lingual gyrus (all p<0.0025, whole brain significant). Importantly, siblings of schizophrenia patients showed several similarities to patients in cerebellar functional connectivity, suggesting that cerebellar dysconnectivity in schizophrenia might be related to familial factors. In conclusion, our findings suggest that dysconnectivity in schizophrenia involves the cerebellum and that this defect may be related to the risk to develop the illness.